Digital-Based Supervision of 21st-Century Skills: An Integrated Evaluation–Supervision Model Using E-MESp 4Cs Mobile - Alya Dwi Arianty; Eny Winaryati; Andari Puji Astuti (Postgraduate, University of Mataram, 2026)
This study examines the implementation of a digital supervision system based on 21st-century skills using the E-MESp 4Cs Mobile platform as an integrated evaluation–supervision model in primary and secondary schools. The research employed an applied research design within a Research, Development, and Diffusion (RD&D) framework, with a specific focus on the implementation evaluation stage. The study involved teachers, principals, and supervisors from Muhammadiyah schools across four regions, comprising an initial pilot phase in Semarang City and an expanded implementation phase in Semarang Regency, Kendal Regency, and Salatiga City. Supervision was conducted through the integration of three core components: lesson planning, instructional implementation, and student learning products, aligned with the competencies of critical thinking, creativity, collaboration, and communication. The findings indicate a recurring gap between documented instructional planning and classroom practices, while instructional implementation and student learning products based on implementation evaluation data generally demonstrated stronger performance across regions. These results suggest that effective instructional practices are not always adequately represented in formal planning documents. The study concludes that digital, data-based supervision can provide a more comprehensive and reflective representation of instructional quality compared to conventional administrative supervision. Within the scope of this implementation-focused study, the E-MESp 4Cs Mobile platform shows potential to support professional development and evidence-based supervisory practices in 21st-century education.